Molecular Modeling and Dynamic Simulation of Arabidopsis Thaliana Carotenoid Cleavage Dioxygenase Gene: A Comparison with Bixa orellana and Crocus Sativus - Priya, R.; Sneha, P.; Rivera Madrid, R.; Doss, C.G.P.; Singh, P.; Siva, R. (John Wiley & Sons, 2017)
Carotenoid cleavage dioxygenase (CCD) gene, ubiquitously found in numerous types of plants, are eminent in synthesizing the various volatile compounds (β-ionone, C13-norisoprenoid, geranylacetone) known as apocarotenoids. These apocarotenoids have various biological functions such as volatile signals, allelopathic interaction and plant defense. In Arabidopsis genome sequence, four potential CCD genes have been identified namely CCD1, CCD4, CCD7, and CCD8. These four genes give rise to diverse biological functions with almost similar sequence identity. In this investigation, an in silico analysis was proposed to study CCD proteins in Arabidopsis thaliana, aiming at constructing three-dimensional (3D) structure for CCD1 proteins of Bixa orellana and Crocus sativus to observe the structural difference among AtCCD (A. thaliana CCD) proteins. The quality of modeled structures was evaluated using RAMPAGE, PSVS protein validation server and Q Mean server. Finally, we utilised molecular dynamics simulation to identify the stability of the predicted CCD protein structures. The molecular dynamic simulation also revealed that AtCCD4 protein showed lesser stability when compared to other CCD proteins. Overall results from molecular dynamics analysis predicted that BoCCD1, CsCCD1, and AtCCD1 show similar structural characteristics.